CFD Analysis of the Effect on Buoyancy Due to Terrain Temperature Based on an Integrated DEM and Landsat Infrared Imagery (2008)
This paper deals with the influence of concrete structures on atmospheric temperatureand the convection winds generated in the Aburra Valley in Medell´ın,Colombia. This area is characterised by low wind velocities with a high industrydensity. A digital elevation model was used from the Radar ShuttleTopography Mission and post-processed in order to obtain a valid volumetricCFD domain. The construction process includes hole-filling due to imperfectionsin the original radar data, decimation of the original cloud-of-points to reduce the excess of detail in regions with low curvature, and the introductionof a volume of air over the terrain surface (CFD domain). Landsat satellitedata was used to set the terrain temperatures for various material compositions.The converted infrared image was then registered into the CFD domainusing an interpolation technique.